BSN2019 conference - an interview with Dr Yemi Akinbamijo (FARA) - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
An interview with Dr Yemi Akinbamijo of FARA on a Radio IITA program - On the spot with Tolu Olabode, during the 32nd Annual International Conference of the Biotechnology society of Nigeria (BSN).